Book review: Todaro, Julie. The post-pandemic library handbook - Maceviciute, Elena (Information Research an international electronic journal, 2023)
Todaro, Julie. The post-pandemic library handbook. Lanham, MD: Rowman & Littlefield, 2022. Xii, 184 p. ISBN 978-1-5381-5375-8